Penggunaan Excel Spreadsheet untuk Penyusunan Laporan Keuagan UMKM Paguyuban Peternak Ayam Banjarejo Magetan - Qimyatussa'adah; Hedi Pandowo; Hamim Tohari; Yana Dwi Chritanti; Yopie Diondy Kurniawan (JURNAL DAYA-MAS, 2021)
Paguyuban Peternak Ayam Banjarejo as a community service partner faces several problems, such as the lack of resources to prepare financial reports that are in accordance with Financial Accounting Standards for Micro, Small and Medium Entities (FAS MSME); the lack of sufficient skills to start systematic financial records using a computer; and the lack of information about the regulations relating to the preparation of financial reports and tax. Therefore, this community service activity is carried out to provide alternative solutions in overcoming obstacles faced by partners. In addition, this activity introduces the use of the simplest technology, like Excel Spreadsheet in preparing financial reports. This community service activity is expected to be an initiation for Partners to apply more sophisticated technology in preparing their financial reports in the future.